Strategic Alignment and Absorptive Capacity as Key Drivers of Marketing Performance and Business Outcomes in Indonesian Food and Beverage MSMEs - Syahyono, Syahyono; S. Syahyono (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2025)
This study explores the role of marketing performance in improving business outcomes for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia’s Food and Beverage (F&B) sector. Specifically, the research examines how strategic alignment and strategy absorptive capacity influence marketing performance and business performance. A quantitative approach using Structural Equation Modeling (SEM) was applied to analyze data from 617 respondents, including owners and managers of F&B MSMEs in West Java. The results indicate that strategic alignment significantly impacts strategy absorptive capacity, which in turn enhances business performance. Additionally, the study highlights the mediating role of strategy absorptive capacity, demonstrating that the alignment of business strategies and the ability to absorb external knowledge directly improve marketing and business outcomes. The research provides practical implications for managers of F&B MSMEs, particularly in adapting their strategies to the dynamic market environment, leveraging digital marketing tools, and fostering organizational capabilities to absorb and apply new knowledge. This study contributes to the literature by integrating strategic alignment, absorptive capacity, and marketing performance into a unified model, offering valuable insights for both academics and practitioners.